Design, Synthesis and Antifungal Evaluation of N-Substituted Maleimide Derivatives with an Imidazole and 2-Methyl Imidazole Moieties (International Journal of Pharmaceutical Sciences and Drug Research, 2023)
A series of N-substituted maleimide derivatives with an attached imidazole and 2-methyl imidazole heterocyclic rings were designed, synthesized and evaluated for their antifungal activity against four pathogenic fungi. The chemical structures of all synthesized compounds were confirmed by 1H NMR, 13C NMR and mass spectra. Initially, all compounds 4a-4g, 5b and 5f were screened for qualitative (zone of inhibition) antifungal activity against C. albicans, A. fumigatus, A. niger, and A. oryzae. The screening results indicate that most of the synthesized compounds showed significant antifungal activity against the tested fungi. Furthermore, the compounds that showed a significant zone of inhibition were selected and tested quantitatively (MIC50 and IC50) against the same pathogenic fungi species. The MIC50 and IC50 results of selected compounds were analyzed. These results strongly suggest that compound 5f has shown promising antifungal activity. Furthermore, the structure–activity relationship of compound 5f revealed that compound substituted with the –F group possess prominent antifungal activity.